1984
DOI: 10.1002/ijc.2910330115
|View full text |Cite
|
Sign up to set email alerts
|

Role of nk cells in the antimetastatic effect of anticoagulant drugs

Abstract: The antimetastatic effects of heparin (40 units) and prostacyclin (PGI2, 100 microgram)1 were investigated in normal mice and in mice with depressed or activated natural killer (NK) cell activity. Both anticoagulants inhibited the formation of lung metastases after inoculation of the FI or F10 sublines of B16 melanoma. Inhibition of NK activity by treatment of mice with anti-asialo GM1 serum abrogated the antimetastatic effects of PGI2 or heparin. Conversely, augmentation of NK-cell activity by poly I:C plus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(60 citation statements)
references
References 20 publications
1
55
2
2
Order By: Relevance
“…This network could protect CTCs against hostile signals including shear stress, modifications of cell-cell and cell-matrix interactions, or immune cells, and would promote their metastatic potential. A mechanism involving a protective role of fibrin and/or platelets in NK-induced cytotoxicity against tumor cells has, for instance, been demonstrated in vitro and using NK-deficient mice in experimental metastasis assays by Degen and colleagues (21,(44)(45)(46)(47)(48). On the other hand, NK-independent processes have also been evidenced (21), one of which implicates the recruitment of monocytes/macrophages in microthrombi favoring the establishment of so-called premetastatic niches (49).…”
Section: Discussionmentioning
confidence: 99%
“…This network could protect CTCs against hostile signals including shear stress, modifications of cell-cell and cell-matrix interactions, or immune cells, and would promote their metastatic potential. A mechanism involving a protective role of fibrin and/or platelets in NK-induced cytotoxicity against tumor cells has, for instance, been demonstrated in vitro and using NK-deficient mice in experimental metastasis assays by Degen and colleagues (21,(44)(45)(46)(47)(48). On the other hand, NK-independent processes have also been evidenced (21), one of which implicates the recruitment of monocytes/macrophages in microthrombi favoring the establishment of so-called premetastatic niches (49).…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant drugs also attenuated metastasis in the same model. About 15 years later Gorelik and colleagues reported that interfering with the hemostatic system prevents metastasis by a NK cell-dependent mechanism (33). Although fibrinogen and factor XIII, components of the plasmatic coagulation system, were found to reduce NK cell reactivity (13,15), the available data point to a more prominent role of platelets for inhibiting NK cell reactivity in metastasis (8).…”
Section: Discussionmentioning
confidence: 99%
“…The latter may promote tumor cell survival, as metastasis is effectively inhibited in the absence of platelets (8)(9)(10). Interestingly, concomitant depletion of platelets and NK cells reverts the antimetastatic phenotype of thrombocytopenic mice (11)(12)(13)(14)(15)(16). It has thus been proposed that platelets may protect tumor cells from NK-dependent antitumor immunity during their passage from the primary tumor to a metastatic site.…”
mentioning
confidence: 99%